Organisational Structure and Employee Commitment of Academic Staff in a Private University in Uganda - Mugizi, Wilson; Nuwatuhaire, Benard; Turyamureeba, Silaji (Journal of Humanities and Social Science, 2019)
This study analysed the relationship between organisational structure (OS) and employee commitment (EC) of academic staff. The aspects of OS that were related to EC were formalisation, centralisation and complexity. This correlational and cross-sectional study was carried out on 145 academic staff of a branch of a private university in Uganda using a self-administered questionnaire. Descriptive analysis, Factor Analysis, Cronbach alpha (α) tests and correlation analysis were carried out. Descriptive analysis revealed that affective commitment of academic staff was high while continuance and normative commitment were moderate. However, the EC index of academic staff indicated that it was moderate. The study also revealed that while implementation of organisational formalisation (OF) and centralisation (OC) was high, for organisational complexity (OX) it was moderate. Factor analysis and Cronbach alpha (α) tests revealed that the items measuring both EC and OS subscales were valid and reliable measures. Correlation analysis revealed a weak positive but significant relationship between OF and OC with EC but for OX it was insignificant. It was concluded that EC of academic staff in private universities in Uganda was a challenge, organisational formalisation was pertinent to promotion of EC but centralisation and complexity were not. It was thus recommended that there should be effective implementation of formalisation in the universities. However, organisational centralisation and complexity may not be over emphasised.
Keywords: Centralisation; Complexity; Employee Commitment; Formalisation; Organizational Structure; Organizational Commitment